Strategy for the Implementation of Autistic Children's Vocational Programs in Special Schools - Lina Dwi Cahya Ningrum; Joko Yuwono; Supriyadi (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
This study aims to determine the strategy for implementing a vocational program for autistic children at Mitra Ananda Autism Special School. This research is qualitative research with a case study approach. Informants in this study were class teachers and vice principals. Informants were taken using the purposive sampling technique. Data was collected using interview, observation, and documentation techniques, with Miles & Huberman interactive model data analysis. The results showed that the implementation of the program consisted of 1) planning, including initial ability assessment, class placement, and program preparation. 2) The learning steps include the implementation of the online-offline system, the use of time, methods, facilities, prompt-reward giving, thematic approaches, and entrepreneurship. 3) Evaluation includes evaluation of the process, results, and parent consultation.